Endovascular treatment of penetrating atherosclerotic ulcers of the arch and thoracic aorta: In-hospital and 5-year outcomesCentral MessagePerspective - Giacomo Murana, MD, PhD; Luca Di Marco, MD, PhD; Mariafrancesca Fiorentino, MD; Francesco Buia, MD; Giorgia Brillanti, BS; Luigi Lovato, MD; Davide Pacini, MD, PhD (JTCVS Open, 2022)
Objective: Thoracic endovascular aortic repair (TEVAR) is the treatment of choice for thoracic aorta diseases including penetrating aortic ulcer (PAU). The objective of this study was to analyze the results of TEVAR for the treatment of PAU in our population. Methods: From January 1999 to January 2019, 830 patients with type B aortic syndromes were treated with TEVAR in our institution. Of these we selected 73 patients treated for a PAU. Clinical and radiologic follow-up was performed in all patients. Results: Mean age of our population was 72 ± 8 years. Fifteen patients (20.5%) were treated in an emergency setting. The proximal landing zone was in arch zone 2 in 22 patients (30.1%). In-hospital mortality was 6.8% and was associated with acute presentation (P = .005). Distal arch delivery of the endograft was unrelated to mortality (Fisher exact test, P = .157). Survival at 1 and 5 years was 81.7% and 67.3%, respectively. Sixteen patients underwent reintervention of the thoracic aorta. Patients who underwent emergency surgery and older patients had a shorter survival (log rank test, P < .001). No difference in survival was shown according to the proximal landing zone (log rank P = .292) or the dimension of the thoracic aorta (log rank P = .067). In multivariable Cox regression analysis, only age older than 75 years was associated with 5-year mortality (hazard ratio, 6.60; 95% CI, 2.12-20.56); P < .001). Conclusions: The use of TEVAR for treatment of aortic PAU is a safe procedure in an elective setting despite necessity of arch stent grafting. An early intervention performed at smaller aortic diameters of <55 mm might be beneficial in selected patients to improve late survival.